Task-related and resting-state fMRI identify distinct networks that preferentially support remembering the past and imagining the future. (February 2018) - Gilmore, Adrian W.; Nelson, Steven M.; Chen, Hung-Yu; McDermott, Kathleen B.
Abstract: The relation between episodic memory and episodic future thought (EFT) remains an active target of research. A growing literature suggests that similar cognitive processes and neural substrates tend to support these acts. However, direct comparisons of whole-brain activity reveal clear differences, with numerous regions more active when engaging in EFT than when remembering, and a smaller collection of regions displaying the opposite pattern of activity. Although various network labels have been applied to prior neuroimaging results, to date no formal resting-state functional connectivity analysis has been conducted. In the current experiment, 48 subjects remembered events from their past and engaged in EFT. Resting-state data were collected from all subjects. Task results replicated recent findings, with more activity during EFT in regions across frontal and parietal cortex, and with more activity during remembering in a smaller number of predominantly parahippocampal and retrosplenial regions. Resting-state connectivity analysis, based on seed locations defined using the fMRI task data, indicated that regions preferentially activated during EFT fell primarily within the default mode network, while those more active during remembering fell primarily within the contextual association network. These results suggest that despite their general similarity, the functional network membership of regions showing task differences is dissociable. We discuss our results in light of several hypotheses that attempt to relate remembering and EFT, and suggest that the data speak to differences in the relative contributions of episodic and semantic memory, as well as controlled and automatic processing, during the acts of remembering or engaging in EFT. Highlights: fMRI identified brain regions related to remembering or imagining personal events. Functional connectivity assessed the network membership of identified regions. Regions associated with remembering recapitulate the contextual association network. Regions associated with imagining recapitulate the default mode network.